Aktivitas Harian Rusa Tutul (Axis axis) pada Lahan Konservasi di Hutan Kota Kecamatan Langsa Baro Kota Langsa - Elfrida Elfrida; Sri Jayanthi; Novita Rahayu (Universitas Islam Negeri Ar-Raniry, 2019)
Spotted deer (Axis axis) is one of the component forming forest ecosystems and has a very important role in the food chain cycle. However, excessive and uncontrolled use of deer by humans can result in a decline in the animal population in nature. One of the conservation efforts that can be done is by captivity (ex-situ conservation). This study was conducted to determine the daily activity of the spotted deer in captivity of the City Forest in Langsa Baro Subdistrict, Langsa City on 8 - 22 February 2018. Data on the daily activities of the spotted deer were obtained through direct observation using the animal sampling scan method for 15 days. The study found that eating was the highest daily activity, namely male 30,84%, female 32,84%, pregnant deer 34,17%, and young deer without horns were 29.08%. The highest activity time is at 08.30-10.30 and the lowest activity time is from 06.00-08.00.